Assessment of morphological, molecular diversity, proximate and sensory properties of superior local durian in Jember District, East Java, Indonesia - VEGA KARTIKA SARI; NURVITTA PRAKASA AGUSTIN IRIAWATI; RIZA YULI RUSDIANA; HALIMATUS SA’DIYAH; SLAMETO SLAMETO; BASUKI BASUKI (Smujo International, 2026)
Abstract. Sari VK, Iriawati NPA, Rusdiana RY, Sa’diyah H, Slameto, Basuki. 2026. Assessment of morphological, molecular diversity, proximate and sensory properties of superior local durian in Jember District, East Java, Indonesia. Asian J Agric 10 (1): g100126. https://doi.org/10.13057/asianjagric/g100126. One of the most valuable fruits in Indonesia is durian (Durio zibethinus). The Panti District in Jember District, East Java, Indonesia, offers an ideal combination of climatic and geographical conditions conducive to durian cultivation. This study aimed to investigate the superior local durian's morphological, molecular, proximate, and sensory diversity. Nine accessions of durian were collected from Panti District. Qualitative characters were evaluated using the Shannon-Wiener diversity index, while quantitative characters were analyzed descriptively to assess morphological diversity. Molecular variation was examined using Random Amplified Polymorphic DNA (RAPD) markers, proximate composition was determined for fruit flesh and seeds, and sensory attributes (taste, aroma, color, texture) were assessed. Results showed coefficients of variation for 10 quantitative characters ranging from 11.47 to 43.3% (low to rather low), and diversity indices for 28 qualitative characters ranging from 0.349 to 1.465 (low to moderate). Five superior durian cultivars from the Panti Jember cluster formed two groups with approximately 30% genetic similarity. The proximal content of durian accessions varies due to differences in genetic material. Sensory tests have high diversity in texture and color characters, which are critical factors influencing consumer preference. These findings provide a basic data for developing effective conservation and breeding strategies to support sustainable durian cultivation.